2018
DOI: 10.14434/josotl.v18i2.22844
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Aging among Graduate Social Work Students: Using Photographs as an Online Pedagogical Activity

Abstract: The United States is experiencing an aging of the population, and by 2030, 20% of Americans will be 65 years or older (Federal Interagency Forum, 2010). However, for many helping professions, including social work, medicine, and nursing, student interest in gerontological practice is quite low. One international study found that only 5.4% of the more than 1,000 social work students who were surveyed indicated that working with older people was their primary area of interest (Author, 2014a). Finding ways to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Four studies (11%) discussed the use of an online discussion board as a way to engage students in after-class discussion or post-online module completion, with variations from student-initiated to instructor-monitored-but-not-engaged to instructors-engaged in the discussion (Boetto & Bell, 2015; Chonody, 2018; Littlefield & Roberson, 2005; Sherwood et al, 2018). Boetto and Bell (2015) described an online learning project on ecological social work in which students were asked to post reflections asynchronously after each workshop and engage in dialogue with peers through their posted responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies (11%) discussed the use of an online discussion board as a way to engage students in after-class discussion or post-online module completion, with variations from student-initiated to instructor-monitored-but-not-engaged to instructors-engaged in the discussion (Boetto & Bell, 2015; Chonody, 2018; Littlefield & Roberson, 2005; Sherwood et al, 2018). Boetto and Bell (2015) described an online learning project on ecological social work in which students were asked to post reflections asynchronously after each workshop and engage in dialogue with peers through their posted responses.…”
Section: Resultsmentioning
confidence: 99%
“…They highlighted that even in the online and asynchronized spaces it is important for instructors to be hyperattentive to power dynamics in students’ participation. In a 6-week asynchronous online course on practice with older adults, students used the discussion board to critically engage with the concept of aging and cultural meanings (Chonody, 2018). The instructor asked each student to post a photo that represents “aging” and reflect on what this image means culturally and personally; students were also given an opportunity to review all photos posted by their peers to explore patterns and cultural meanings.…”
Section: Resultsmentioning
confidence: 99%
“…Bowers (2017) used Photovoice as a method of engaging social work students in critical reflection and found that using Photovoice allowed students to reflexively analyse and develop their professional identities and consider what that meant for their practice. In addition to Bowers (2017) study, I identified 7 other studies that utilised Photovoice with social work students with various research aims (Bailey-McHale et al, 2019; Bowers, 2017; Bromfield and Capous-Desyllas, 2017; Byrne et al, 2009; Chonody, 2018; Morley et al, 2017; Phillips and Bellinger, 2010; Walsh et al, 2015). Other studies identified in initial scoping reviews of the topic utilised similar photo-elicitation methods but with a sample of university or college students from other subjects; all indicated in their findings that photography based research methods were more effective than traditional methods, such as observation or interviews at engaging student participation (Anderson, 2016; Patka et al, 2017).…”
Section: Existing Literaturementioning
confidence: 99%
“…The study was designed with a view to working collaboratively with participants, following the principles set out in Participatory Action Methodology ( Liamputtong, 2008 ) and Photovoice ( Wang and Burris 1997 ) was selected as the primary data collection tool. Photovoice has been found to be an effective research method and teaching method for social work research and pedagogy ( Bailey-McHale et al, 2019 ; Chonody, 2018 ) because of its need for collaboration between participants and facilitator and its focus on reflexivity and anti-oppressive practice, all of which are essential skills for social workers to develop ( Jarldon, 2019 ). Once participants had captured their images, they wrote captions to accompany them and then presented them at a later focus group.…”
Section: Introductionmentioning
confidence: 99%